2017
DOI: 10.1111/vop.12504
|View full text |Cite
|
Sign up to set email alerts
|

Cofactors associated with Sudden Acquired Retinal Degeneration Syndrome: 151 dogs within a reference population

Abstract: Objective To determine factors associated with sudden acquired retinal degeneration syndrome (SARDS) diagnosed within one referral population. Animals Studied 151 dogs diagnosed with SARDS. Procedures Breed, age, sex, and body weight were compared between dogs with electroretinogram-confirmed SARDS and dogs presented to the UC Davis Veterinary Medical Teaching Hospital (UCD-VMTH) from 1991 to 2014. Results SARDS was diagnosed in 151 dogs, representing 1.3% of dogs presented to the UCD-VMTH for ophthalmic disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0
15

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(42 citation statements)
references
References 30 publications
(74 reference statements)
5
22
0
15
Order By: Relevance
“…Sudden Acquired Retinal Degeneration Syndrome was first reported almost four decades ago; however, the precise etiology of the disease is still being extensively debated without a clear consensus on its exact nature . SARDS is most frequently seen in middle aged/older females of small breeds, with mixed‐breed dogs, Dachshunds, Pugs, and Miniature Schnauzers being the most frequently affected, which corresponds to our findings in this study . Previous studies found a relatively high incidence of metabolic abnormalities, such as polyuria and polydipsia (38%, 30%), polyphagia (19%, 20%), and alkaline phosphatase elevation (37%, 28%), which was also in good accord with our findings in similar percentages.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Sudden Acquired Retinal Degeneration Syndrome was first reported almost four decades ago; however, the precise etiology of the disease is still being extensively debated without a clear consensus on its exact nature . SARDS is most frequently seen in middle aged/older females of small breeds, with mixed‐breed dogs, Dachshunds, Pugs, and Miniature Schnauzers being the most frequently affected, which corresponds to our findings in this study . Previous studies found a relatively high incidence of metabolic abnormalities, such as polyuria and polydipsia (38%, 30%), polyphagia (19%, 20%), and alkaline phosphatase elevation (37%, 28%), which was also in good accord with our findings in similar percentages.…”
Section: Discussionsupporting
confidence: 92%
“…1 SARDS is most frequently seen in middle aged/older females of small breeds, with mixed-breed dogs, Dachshunds, Pugs, and Miniature Schnauzers being the most frequently affected, which corresponds to our findings in this study. 2,3,24,25 Previous studies found a relatively high incidence of metabolic abnormalities, such as polyuria and polydipsia (38%, 2 30% 3 ), polyphagia (19%, 2 20% 3 ), and alkaline phosphatase elevation (37%, 2 28% 3 ), which was also in good accord with our findings in similar percentages. The most recent study of a Canadian patient population, however, revealed much higher incidence of metabolic abnormalities in SARDS patients.…”
Section: Discussionsupporting
confidence: 92%
“…Sudden acquired retinal degeneration syndrome (SARDS) is a common cause of incurable vision loss in dogs seen by veterinary ophthalmologists . It is characterized by an acute loss of vision in initially ophthalmoscopically normal eyes combined with an extinguished electroretinogram (ERG) . The typical signalment of dogs with SARDS is a middle aged to older, moderately overweight, mixed breed dog .…”
Section: Introductionmentioning
confidence: 99%
“…1 It is characterized by an acute loss of vision in initially ophthalmoscopically normal eyes combined with an extinguished electroretinogram (ERG). [1][2][3][4][5][6][7][8][9][10] The typical signalment of dogs with SARDS is a middle aged to older, moderately overweight, mixed breed dog. [4][5][6][9][10][11] Transient clinical signs including polyuria, polydipsia and polyphagia are present in up to 85% of dogs diagnosed with SARDS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation